MRI Contrast Agents From Molecules to Particles - Laurent, Sophie; Henoumont, Céline; Stanicki, Dimitri; Boutry, Sébastien; Lipani, Estelle; Belaid, Sarah; Muller, Robert N.; Vander Elst, Luce.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book describes the multiple aspects of (i) preparation of the magnetic core, (ii) the stabilization with different coatings, (iii) the physico-chemical characterization and (iv) the vectorization to obtain specific nanosystems. Several bio-applications are also presented in this book. In the early days of Magnetic Resonance Imaging (MRI), paramagnetic ions were proposed as contrast agents to enhance the diagnostic quality of MR images. Since then, academic and industrial efforts have been devoted to the development of new and more efficient molecular, supramolecular and nanoparticular systems. Old concepts and theories, like paramagnetic relaxation, were revisited and exploited, leading to new scientific tracks. With their high relaxivity payload, the superparamagnetic nanoparticles are very appealing in the context of molecular imaging but challenges are still numerous: absence of toxicity, specificity, ability to cross the biological barriers, etc. .
Nanomaterials in medicine -- Magnetic properties (diamagnetism, paramagnetism, ferromagnetism, ferrimagnetism, antiferromagnetism, superparamagnetism) -- Imaging probes -- Magnetic resonance imaging (MRI) -- Bases of MRI -- MRI contrast agents -- Paramagnetic gadolinium complexes -- Superparamagnetic iron oxide nanoparticles -- Synthesis of magnetic nanoparticles -- Stabilization of magnetic nanoparticles -- Physico-chemical characterization of nanoparticles -- MRI applications -- Conclusions.
Keywords: Biomedical engineering; Biomaterials; Microtechnology; Microelectromechanical systems; Medicine -- Research; Biology -- Research; Medical physics; Biomedical Engineering and Bioengineering; Biomaterials; Microsystems and MEMS; Biomedical Research; Medical Physics